Vertical Distribution of Heavy Metal in Soil of Abandoned Vehicles Dismantling Area - Wu, Yanyu; Peng, Xiaochun; Hu, Xiaoying (Asian Journal of Chemistry, 2013)
In order to study heavy metal contamination in the soil of the abandoned vehicles dismantling area, the soil samples with vertical depth 0-1000 cm were collected and the physical and chemical characterizations of heavy metals e.g., Cu, Zn, Pb, Cr, Ni, Cd, Hg and As were analyzed. The correlation matrix was applied to evaluate the heavy metal contamination degree of soil samples. Moreover, the fractions of Pb and Zn in soils of various vertical depths were investigated. The results indicated that a certain degree of pollution had been caused in the superficial soil by heavy metals Cu, Zn, Pb, Cr, Ni, Cd, Hg and As, where the contamination levels of Pb, Zn, Cu excessed significantly. A combined pollution characterization of Cu, Zn, Pb, Cr, Ni, Hg and As was also presented. In addition, the concentrations of heavy metals in soils samples decreased exponentially with increasing the vertical depth, whereas the accumulated sub-standard depth of heavy metals Pb and As were still up to 150 cm. The content of exchangeable ion state of Pb was lowest. The pH control functions in species of Pb of soil were not significant. With the soil of vertical depth increasing, the ratios of oxidizable Pb and light acidic soluble Pb reduced rapidly and the residual Pb increased gradually. The exchangeable ion state Zn and weak acid soluble Zn significantly correlated with the soil pH values. The main fraction of Zn in light acidic soil was exchangeable ion state and the main fractions of Zn in neutral soil were reducible and oxidizable fractions.